Learning Politics through Entertainment: Exploring the Effects of Biographical Films on Political Learning and Attitude Toward Female Politicians. Issue 2 (15th March 2021) - Rasul, Azmat; Raney, Arthur A
ABSTRACT: This study examined the effects of semi-fictional biographical political films on political learning and attitude change in audiences of fictionalized accounts of female politicians. Data from 310 participants indicated that content-related political learning significantly increased and attitude toward female politicians positively changed after exposure. A conceptual model of the political entertainment effects indicated that initial political learning transported the audience into the biographical narrative, which led to greater enjoyment, as well as learning gain and a positive attitude toward female politicians. Our findings provide important clarification to existing research and offer both theoretical, methodological, and practical implications.